Pregnant woman suffered from thrombocytopenia - Leonid I. Dvoretsky (LLC "MEDIAFORMAT", 2023)
The paper reports the major clinical situations associated with thrombocytopenia in pregnancy. The diagnostic criteria of the most frequent disorders associated with thrombocytopenia that occur during gestation are provided. The issues related to differential diagnosis of thrombocytopenia in pregnancy are discussed.